Localization of self-interacting domains within betaretrovirus Gag polyproteins - Zábranský, Ales; Sakalian, Michael; Pichová, Iva (Virology, 2005)
The Betaretrovirus genus is characterized by the ability to preassemble immature capsids within the cytoplasm. For Mason-Pfizer monkey virus (M-PMV) this ability depends in part upon the unique Internal Scaffold Domain (ISD) within the p12 region of Gag. In this study, we have further characterized the ability of M-PMV p12 to promote Gag-Gag interaction and have examined the Gag polyprotein of the related mouse mammary tumor virus (MMTV) to potentially identify a region with equivalent function. Using the yeast two-hybrid system, we confirmed that both Gag polyproteins strongly interact, primarily through the CA-NC regions, but also through additional domains N-terminal to CA. For M-PMV, this auxiliary interaction domain was p12. For MMTV, no single strongly self-interacting protein was identified. Instead, MMTV Gag appears to utilize the weak contributions of several protein domains to support the main interaction of its CA-NC. Our findings suggest that, in addition to the canonical NC "I-domain" interaction, MMTV Gag self-association results from the concerted action of multiple regions of the polyprotein while M-PMV Gag relies mainly on its p12 domain.
Keywords: Molecular Sequence Data; sekvence aminokyselin; Mason-Pfizer monkey virus; kapsida; polymerázová řetězová reakce; Mammary Tumor Virus, Mouse; Polymerase Chain Reaction; DNA primery; virus myšího tumoru prsní žlázy; Capsid; Base Sequence; sekvence nukleotidů; Gene Products, gag; Escherichia coli; zvířata; Binding Sites; Amino Acid Sequence; Plasmids; plazmidy; genové produkty gag; molekulární sekvence - údaje; DNA Primers; Masonův-Pfizerův opičí virus; vazebná místa; Animals